2017
DOI: 10.1002/cncr.30699
|View full text |Cite
|
Sign up to set email alerts
|

Relative effectiveness of adjuvant chemotherapy for invasive lobular compared with invasive ductal carcinoma of the breast

Abstract: Adjuvant chemotherapy was not associated with improved OS for patients with ER-positive, HER2-negative, stage I/II ILC. Avoidance of ineffective chemotherapy will markedly reduce the adverse effects and economic burden of breast cancer treatment for a large proportion of patients with breast cancer. Cancer 2017;123:3015-21. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 22 publications
2
50
0
3
Order By: Relevance
“…Consistent with these features, ILC patients have a relatively favorable 5-year survival rate. However, these tumors show local recurrence, exhibit diminished response to hormone and chemotherapy compared with invasive ductal carcinoma (IDC) ( Metzger Filho et al, 2015 ; Marmor et al, 2017 ), and can recur as lethal tumors many years after treatment ( Korhonen et al, 2013 ; Pestalozzi et al, 2008 ; Colleoni et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with these features, ILC patients have a relatively favorable 5-year survival rate. However, these tumors show local recurrence, exhibit diminished response to hormone and chemotherapy compared with invasive ductal carcinoma (IDC) ( Metzger Filho et al, 2015 ; Marmor et al, 2017 ), and can recur as lethal tumors many years after treatment ( Korhonen et al, 2013 ; Pestalozzi et al, 2008 ; Colleoni et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the data from the Netherlands Cancer Registry, for patients with early-stage (pathologically assessed T1 and T2) cancers, patients with ILCs were less likely to undergo breast conserving surgery (43% vs. 54%) than those with ductal cancers 15 . Specific to lobular cancers, two large independent studies using data from the Netherlands Cancer Registry 16 and from the California Cancer Registry 17 , have shown that the combination of adjuvant chemotherapy and adjuvant hormonal therapy did not improve 10-year survival rates over adjuvant hormonal therapy alone.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that adjuvant chemotherapy did not confer an additional benefit in patients with lobular cancer . In addition, a more recent study by Marmor et al addressed the impact of adjuvant chemotherapy in the survival of patients with invasive lobular vs invasive ductal cancer within a California data registry. In this study, likewise, adjuvant chemotherapy did not improve outcomes in 4638 patients with ER+ stage I/II invasive lobular cancer.…”
Section: Discussionmentioning
confidence: 99%